Histopathological effects of chlorpyrifos on the gills, hepatopancreas and gonads of the freshwater crab Zilchiopsis collastinensis. Persistent effects after exposure - Negro, Carlos Leandro (2017)
Sublethal effects of the pesticide chlorpyrifos were evaluated in the crab Zilchiopsis collastinensis (Decapoda, Trichodactylidae). Crabs were exposed to high concentrations of chlorpyrifos at the beginning of the experiment and controlled dilution, under natural light and temperature conditions. A control and three concentrations (22.4, 41.25 and 61.4 µg chlorpyrifos L−1) were evaluated in triplicate. Nine crabs per concentration and day were used. The gills, hepatopancreas and ovaries were sampled before pesticide exposure (day 0) and 8, 15 and 22 days later, when concentrations were diluted and below the detection limits. The histopathological effects and their variations in time were observed and quantified. In gills, hyperplasias were observed in several cases, mainly in crabs exposed to chlorpyrifos. The number of collapsed lamellae and the number of affected lamellae quickly increased in exposed crabs, as effects were observed on day 8 and remained until day 22. In hepatopancreas there was an increase in the number of F and B -cells and affected tubules, especially after 22 days of exposure (p<0.05). In ovaries, there were no effects on gonadosomatic indexes or oocyte volume, but there was a significant increase in the atretic oocyte proportion related to pesticide exposure (p<0.05). The histopathological effects on the gills, hepatopancreas and ovaries were observed after exposure and persist even after dilution, and might be related to earlier exposures. Thus, these histopathological effects might be used as pesticide biomarkers even after the pesticide is not detected by chemical methods.